2022
DOI: 10.1111/os.13200
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Anesthesia Combined with Tranexamic Acid Reduces Perioperative Blood Loss in Simultaneous Bilateral Total Hip Arthroplasty: A Retrospective Cohort Study

Abstract: Objective: To assess the efficacy and safety of hypotensive anesthesia (HA) combined with tranexamic acid (TXA) for reducing perioperative blood loss in simultaneous bilateral total hip arthroplasty (SBTHA). Methods:In this retrospective cohort study, a total of 183 eligible patients (15 females and 168 males, 44.01 AE 9.29 years old) who underwent SBTHA from January 2015 to September 2020 at our medical center were enrolled for analysis. Fifty-nine patients received standard general anesthesia (Std-GA group),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…In line with the findings of this study, the results of Zhang et al's study also indicated the effectiveness of the combination of CHA and TXA in reducing blood loss and transfusion after the surgery such that the total blood loss and blood transfusion rates in this approach were approximately 30% and 15%, respectively (25). In addition, they stated that Hb and HCT levels were better maintained by administering TXA plus CHA (25). In fact, a faster recovery indicated by the reduced length of hospital stay in the two CHA groups was experienced after the surgery by improving the HCT and Hb levels.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with the findings of this study, the results of Zhang et al's study also indicated the effectiveness of the combination of CHA and TXA in reducing blood loss and transfusion after the surgery such that the total blood loss and blood transfusion rates in this approach were approximately 30% and 15%, respectively (25). In addition, they stated that Hb and HCT levels were better maintained by administering TXA plus CHA (25). In fact, a faster recovery indicated by the reduced length of hospital stay in the two CHA groups was experienced after the surgery by improving the HCT and Hb levels.…”
Section: Discussionsupporting
confidence: 88%
“…The study population included all infants that were candidates for craniosynostosis correction surgery and were referred to Imam Hossein Hospital affiliated to Isfahan University of Medical Sciences, from April 2017 to June 2018. In this study, 75 patients were considered as the sample according to the sample size formula in between-groups comparison, at the confidence level of 95%, the test power of 80%, and considering the results of previous studies ( 25 ) reporting the mean and standard deviation of the total blood loss in control and TXA plus CHA groups equal to 1850.83 ± 800.73 ml and 1377.74 ± 423.46 ml, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has also been reported to improve the visibility of the surgical field and shorten the operative time 11,12 . Hypotensive anesthesia is mainly used in the fields of orthopedic spine surgery and total hip replacement; however, it is also known to reduce intraoperative blood loss in patients undergoing orthognathic surgery and was also adopted for this study [13][14][15] .…”
Section: Original Articlementioning
confidence: 99%